1988
DOI: 10.1159/000238539
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Cefuroxime and Ceftazidime into Human Lungs

Abstract: We have studied the penetration of cefuroxime and ceftazidime into lung tissue of 40 patients subjected to pulmonary surgery. Samples of blood and lung tissue were taken 1 and 2 h after antibiotic administration. Patients were randomly assigned to four dosage schedule groups: group A received a single intravenous injection of 750 mg cefuroxime; the lung tissue levels at 1 and 2 h were 9.6 ± 3.1 and 4.54 ± 2.64 μg/g of cefuroxime; the percentage penetration from serum into the lung tissue was 33.7 and 34.6%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The concentration of cefuroxime used in our experiments covers a range of serum and intrapulmonary concentrations after oral and continuous i.v. administration in humans [31-34]. Additionally we used a concentration of cefuroxime (62.5 mg/L) above these therapeutic intrapulmonary concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of cefuroxime used in our experiments covers a range of serum and intrapulmonary concentrations after oral and continuous i.v. administration in humans [31-34]. Additionally we used a concentration of cefuroxime (62.5 mg/L) above these therapeutic intrapulmonary concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the most important pharmacokinetic parameter for the killing effect of cephalosporins in vivo is the time above MIC (4). Finally, levels in lung tissue of 17.1 g/ml at 1 h and 14.7 g/ml at 2 h have been attained after 750 mg of intravenous cefuroxime (11).…”
mentioning
confidence: 90%
“…In a second group of 10 patients, given three doses of 750 mg cefuroxime, the tissue levels were 17.1__7.7 and 14.7_+5.4 ~g/g and the percentage of penetration was 89.1 and 102.8 at 1 and 2 h, respectively [36].…”
Section: Lung Tissuementioning
confidence: 94%